2021
DOI: 10.1111/jcmm.16467
|View full text |Cite
|
Sign up to set email alerts
|

Two novel qualitative transcriptional signatures robustly applicable to non‐research‐oriented colorectal cancer samples with low‐quality RNA

Abstract: Currently, due to the low quality of RNA caused by degradation or low abundance, the accuracy of gene expression measurements by transcriptome sequencing (RNA‐seq) is very challenging for non‐research‐oriented clinical samples, majority of which are preserved in hospitals or tissue banks worldwide with complete pathological information and follow‐up data. Molecular signatures consisting of several genes are rarely applied to such samples. To utilize these resources effectively, 45 stage II non‐research‐oriente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Previous studies demonstrated that relative expression ordering (REO)-based signatures were robust across different data sets [16]. Cheng et al [17] have demonstrated that the REO patterns of gene pairs were insensitive to tumour purities of samples. Moreover, the REO-based signature could be applied to the individual patient using within-sample REOs [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that relative expression ordering (REO)-based signatures were robust across different data sets [16]. Cheng et al [17] have demonstrated that the REO patterns of gene pairs were insensitive to tumour purities of samples. Moreover, the REO-based signature could be applied to the individual patient using within-sample REOs [18].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al . [ 17 ] have demonstrated that the REO patterns of gene pairs were insensitive to tumour purities of samples. Moreover, the REO‐based signature could be applied to the individual patient using within‐sample REOs [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput sequencing methods and next-generation omics platforms have enabled the unparalleled molecular profiling of various diseases in recent years [ 11 ]. Transcriptome sequencing has become the primary tool for measuring gene expression owing to technological advancements and its lower costs [ 12 ]. Furthermore, the remarkable bioinformatic revolution has led to the generation of a vast quantity of data that could be utilized to map out information about all known genes and cancer types and identify useful patterns [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the advance of sequencing technology and rapid reduction in costs, transcriptome sequencing (RNA-Seq) has been widely used in gene expression measurement [ 22 ]. Plant metabolites reflect their responses to biological and abiotic stimuli, serving as a connecting link between genotype and phenotype [ 23 ].…”
Section: Introductionmentioning
confidence: 99%